PESAN MORAL PADA FILM ANIMASI NUSSA EPISODE “TIDUR SENDIRI, GAK TAKUT!” - Elsa Mutia Sandra, Dr. Syafwandi, M.Sn., (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
This article aims to describe the meaning of the sign contained in the animated film Nussa episode "Sleep Alone, Not Afraid!", which produces a moral message that is useful for the audience. This article is based on research that indirectly produces moral messages conveyed by characters through verbal and visual elements based on the scenes that occur in this episode. The approach uses semiotics theory and color theory. Qualitative research methods with data analysis techniques Miles and Huberman. The researcher describes pieces of the scene to identify signs in the form of verbal symbols (words / sounds) and visual symbols of characters (expressions, gestures, and  colors), which the researcher will then analyze by looking at two levels of meaning, denotation and connotation. Nussa animated film episode "Sleep Alone, Not Afraid!" As a whole contains meaning that is presented through verbal and visual symbols. The symbol contained in the episode "Sleep Alone, Not Afraid!" Means the morality of Muslims.Keywords: Animation, Nussa, Moral Messages and Semiotic